The Lorax - Dr Seuss (HarperCollins Children's Books, 2012)
The story of The Lorax is part of the Dr Seuss Classic Collection. A hilarious story with typical zany humour and silly rhymes, that packs a punch with its ecological message without feeling heavy-handed or worthy.
Keywords: Juvenile literature-Fiction